Trust, Information Quality, and Reputation: Determinants of Tourist Interest in Lake Toba, Indonesia - Erizal; Widodo, Slamet (Sinergi International Journal of Economics, 2023)
Lake Toba has attracted the attention of both local and international tourists. In efforts to enhance tourists' interest in visiting Lake Toba, it is crucial to understand the factors influencing tourists' decisions. This research analyzes the influence of trust, information quality, and reputation on tourists' interest in visiting Lake Toba. Using quantitative methods and Partial Least Squares (PLS) techniques, data were collected from 200 tourists visiting in June 2024. The results indicate that all three variables significantly and positively impact tourists' interest. Trust enhances tourists' confidence in a positive experience, information quality aids decision-making, and a good reputation serves as an indicator of destination quality and safety. Research recommendations include exploring other influencing factors and conducting similar studies in different destinations.